2023
DOI: 10.1007/s00170-022-10655-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of chip formation of Ti–6Al–4V in oxygen-free atmosphere

Abstract: Titanium and titanium alloys have high strength at low density, good corrosion resistance and excellent biocompatibility. Therefore, the use of titanium materials is well established in high-performance applications such as aerospace and biomedical. However, titanium and titanium alloys such as Ti–6Al–4 V have low thermal conductivity, exhibit unfavorable chip formation with typical segmented chips and have high chemical affinity to surrounding elements such as oxygen. Tool wear and the properties of the compo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…Denkena et al [46] investigated chip formation in Ti-6Al-4V under different atmospheres during orthogonal cutting. They found that the surrounding atmosphere significantly affects chip formation, with non-periodic segmentation under oxygen-free conditions and segmental chip formation under air.…”
Section: Introductionmentioning
confidence: 99%
“…Denkena et al [46] investigated chip formation in Ti-6Al-4V under different atmospheres during orthogonal cutting. They found that the surrounding atmosphere significantly affects chip formation, with non-periodic segmentation under oxygen-free conditions and segmental chip formation under air.…”
Section: Introductionmentioning
confidence: 99%